Associations Between Wearing Masks and Respiratory Viral Infections: A Meta-Analysis and Systematic Review - Yiming Chen; Yuelin Wang; Ningbin Quan; Jun Yang; Jun Yang; Yinyin Wu (Frontiers Media S.A., 2022)
BackgroundRespiratory viral infections (RVIs) are a major health concern, and some previous studies have shown that wearing masks was effective in preventing RVIs, while others failed to show such effect. Therefore, a systematic review and meta-analysis was conducted to investigate the effectiveness of wearing masks.MethodsPubMed, ScienceDirect, Web of Science, the Cochrane Library, EMBASE, MEDLINE, China National Knowledge Infrastructure (CNKI), and Chinese Scientific Journal Database (VIP database) were searched for studies evaluating the effectiveness of wearing masks. The risk ratio (RR) was used to measure the effectiveness of wearing masks in preventing RVIs for randomized controlled trials (RCTs) and cohort studies, and the odds ratio (OR) was used for case-control studies. Forest plots were used to visually assess pooled estimates and corresponding 95% CIs. The I2 test was used to examine the heterogeneity, and subgroup analysis was used to explore the possible explanations for heterogeneity or compare the results between subgroups. Sensitivity analysis was conducted to assess robustness of the synthesized results. Begg's test and Egger's test were used to assess the publications bias.ResultsThirty-one studies (13,329 participants) were eligible for meta-analyses. Overall, the results showed that wearing masks was effective in preventing RVIs. The sensitivity analysis showed that the results of those meta-analyses were robust and reliable. There was no significant publication bias in meta-analysis of case-control studies and most subgroup analyses.ConclusionsWearing masks might be effective in preventing RVIs. To reduce their RVI risk, people should wear masks when they go out in public.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier: CRD42021296092.